Expanding our understanding of military social work: The concept of military- and veteran-connected populations. Issue 1 (28th February 2017) - Martin, James; Albright, David; Borah, Elisa
Abstract: Cultural competence is the cornerstone of engagement in the helping professions. This article is intended to introduce and describe the concept of military- and veteran-connected populations with the intent of promoting awareness of the many individuals in our society whose lives are impacted by military service.